2020
DOI: 10.1002/ccd.29435
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography analysis of late lumen enlargement after paclitaxel‐coated balloon angioplasty for de‐novo coronary artery disease

Abstract: Background Paclitaxel‐coated balloon angioplasty for de‐novo coronary artery lesions causes late lumen enlargement (LLE), however, the mechanisms and predictors of LLE have not been elucidated. Methods and Results We retrospectively analyzed 91 consecutive patients with 95 de‐novo coronary lesions, who underwent paclitaxel‐coated balloon angioplasty without stenting from August 2018 to July 2019 as well as follow‐up coronary angiography and optical coherence tomography (OCT). The mean follow‐up duration was 8.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…In our study, LLL was considerably lower in DCB group than in DES group (0.06 ± 0.61 vs. 0.41 ± 0.64 mm, P < 0.001) and QCA results demonstrated that a total of 46.3% of lesions appeared late lumen enlargement. The phenomenon of de novo lesions after DCB angioplasty has also been reported in other studies (21)(22)(23)(24)(25)(26). This phenomenon has positive significance in particular lesions, such as CTO and small-vessel disease.…”
Section: Discussionsupporting
confidence: 74%
“…In our study, LLL was considerably lower in DCB group than in DES group (0.06 ± 0.61 vs. 0.41 ± 0.64 mm, P < 0.001) and QCA results demonstrated that a total of 46.3% of lesions appeared late lumen enlargement. The phenomenon of de novo lesions after DCB angioplasty has also been reported in other studies (21)(22)(23)(24)(25)(26). This phenomenon has positive significance in particular lesions, such as CTO and small-vessel disease.…”
Section: Discussionsupporting
confidence: 74%
“…This form of dissection was termed "therapeutic dissection" [29], which does not significantly compress the coronary lumen, affect blood flow, or cause adverse events, allowing patients to be discharged as scheduled. Studies have shown that restenosis of this dissection type is uncommon [30][31][32]; however, more angiographic follow-up data is required to determine if dissection after DCB is beneficial for positive vascular remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Late angiographic findings can also provide important insight into arterial remodeling following a DCB-only approach, even with a small number of patients. Previous angiographic and intravascular imaging analyses [24][25][26] reported late lumen enlargement (LLE) in 50%-70% of cases following DCB angioplasty in non-CTO lesions. In our study, even in CTO lesions, 57.8% (37 of 64 lesions)…”
Section: Discussionmentioning
confidence: 99%